Zebrafish foggy/spt5 is required for migration of facial branchiomotor neurons but not for their survival - Cooper, Kimberly L. (2005)
Transcript elongation is a critical step in the production of mature messenger RNAs. Many factors have been identified that are required for transcript elongation, including Spt5. Studies in yeast determined that spt5 is required for cell viability, and analyses in Drosophila indicate Spt5 is localized to sites of active transcription suggesting it is required generally for transcription. However, the requirement for spt5 for cell viability in a metazoan organism has not been addressed. We determined that zebrafish foggy/spt5 is required cell-autonomously for the posterior migration of facial branchiomotor neurons from rhombomere 4 (r4) into r6 and r7 of the hindbrain. These genetic mosaics also give us the unique opportunity to determine if spt5 is required for mRNA transcription equivalently at all loci by addressing two processes within the same cell — neuronal migration and cell viability. In a wild-type host, spt5 null facial branchiomotor neurons survive to at least 5 days post fertilization (dpf) while failing to migrate posteriorly. This indicates that spt5-dependent transcript elongation is required cell autonomously for a complex cell migration, but not for the survival of these same cells. This work provides evidence that transcript elongation is not a global mechanism equivalently required by all loci, and may actually be under more strict developmental regulation.